Prognostic significance of eighth edition TNM stage criteria in combined small-cell lung cancer - Zhao, Ziran; Gao, Yibo; Tan, Fengwei; Xue, Qi; Gao, Shugeng; He, Jie (Frontiers in Oncology, 2023)
Objectives This study aimed to evaluate the prognostic significance of the eighth edition TNM stage criteria in patients with combined small-cell lung cancer (C-SCLC) on a population level. Methods Using the Surveillance, Epidemiology, and End Results (SEER) database, patients diagnosed with C-SCLC (histology code 8245) between the years 2004 and 2015 were identified. We performed a Kaplan–Meier analysis and used the multivariable cox regression proportional hazards model to obtain prognostic overall survival estimates for each group of patients. Results A total of 477 patients diagnosed with C-SCLC were identified. The T, N, M, TNM, and combined TNM stage status of the eighth edition were all significant prognostic factors for patients’ overall survivals, with the best discrimination identified in the combined stages. Surgery was also found to be a prognostic factor (HR =1.95, 95%CI =1.49-2.56, p<0.01) for patients with C-SCLC. Conclusions The combined eighth edition of the TNM staging criteria shows reliable prognostic significance in patients with C-SCLC. Moreover, surgery might be significant for improving the patients’ prognosis.